The reactivity of an inorganic glass melt with ZIF-8 - Longley, Louis; Calahoo, Courtney; Southern, Thomas J. F.; Evans, Rachel C.; Wondraczek, Lothar; Bennett, Thomas D. (Dalton Transactions, 2021)
The thermal behaviour of ZIF-8, Zn(meIm)2in the presence of a sodium fluoroaluminophosphate glass melt was probed through differential scanning calorimetry and thermogravimetric analysis. The structural integrity of ZIF-8 was then determined by a combination of powder X-ray diffraction, Fourier transform infra-red and1H nuclear magnetic resonance spectroscopy.
CRIS-Team Scopus Importer:2023-04-20